Non Dispersive Chemical Deacidification of Crude Palm Oil in Hollow Fiber Membrane Contactor - Purwasasmita, Mubiar; Nabu, Eryk Bone Pratama; Khoiruddin, K.; Wenten, I Gede (Journal of Engineering and Technological Sciences, 2015)
Performance of chemical deacidification of crude palm oil (CPO) using aqueous NaOH solution in a polysulfone hollow fiber ultrafiltration membrane wasÂ  investigated. The effects of operating temperature, NaOH concentration and flow rates on percentage of free fatty acids (FFA) removal, oil loss, soap entrainment and overall mass transfer coefficientÂ  wereÂ  evaluated. Overall mass transfer coefficients, soap content in oil and neutral oil loss all increasedÂ  when theÂ  temperatureÂ  was increased from 60 to 70Â°C due to an increase of the FFA distribution value. A minimum 0.25 N of NaOH or a NaOH to FFAÂ  molar ratioÂ  of about 7.62 wasÂ  required to facilitate the expected extraction efficiency. The increased oil flowrate slightly enhanced the solute transport kinetics,Â  while theÂ  aqueous phase flowrate did not significantly influence deacidification efficiency or mass transfer coefficient. About 97% of FFA removal was achieved within 4 hours. The maximum oil loss observed was 11% and the highestÂ  soap content in theÂ  oil without separation step was 3150 ppm. The valuesÂ  of theÂ  overall mass transfer coefficient variedÂ  from 2.97Ã10-7 to 7.71Ã10-7 m/s. These results show the potential of using the non dispersive membrane contacting process for chemical deacidification of CPO as well as other vegetable oils.